2020
DOI: 10.1186/s40594-020-00240-5
|View full text |Cite
|
Sign up to set email alerts
|

Do inquiry-based teaching and school climate influence science achievement and critical thinking? Evidence from PISA 2015

Abstract: Background: Inquiry-based teaching (IBT) and improving school climate are the two most commonly used strategies for fostering learning and critical thinking skills in students. IBT has positioned itself as one of the most recommended "active" methodologies for developing intellectual autonomy and complex thought processes, whereas school climate is considered to be a protective factor that helps mitigate adverse conditions and has a positive impact on teaching and learning. This study investigates the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 19 publications
2
24
0
1
Order By: Relevance
“…Consistent with previous studies also [45,52], three important predictors in the SVM model relate to students' perceptions regarding their social experiences in school. BEING-BULLIED is the index that measures students' exposure to bullying, and the poor reading proficiency students report higher values on this index.…”
Section: Social Experiences In Schoolsupporting
confidence: 86%
“…Consistent with previous studies also [45,52], three important predictors in the SVM model relate to students' perceptions regarding their social experiences in school. BEING-BULLIED is the index that measures students' exposure to bullying, and the poor reading proficiency students report higher values on this index.…”
Section: Social Experiences In Schoolsupporting
confidence: 86%
“…In a follow-up experimental context, the SLA can also be distributed as a pre-and post-test to compare diverse teaching methods or integrated in longitudinal analyses to report modification in demonstrated knowledge, beliefs, and values. Inquiry-based teaching, group dialogue and STEM-based teaching, game-based teaching can improve students' SL (Botes, 2022;Gómez & Suárez, 2020;Pebriani et al, 2022;Peffer & Ramezani, 2019;Suryaningsih et al, 2022;Wang et al, 2022;Warfa et al, 2018;Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the 2015 Trends in International Mathematics and Science Study (TIMSS) have indicated that inquiry-based instruction is positively correlated with student learning outcomes (Teig, 2021;Teig et al, 2018). However, a secondary analysis of PISA 2015 data from Taiwan (Liou, 2021) and 72 countries revealed a negative association between inquiry-based teaching and students' scientific literacy (Gómez & Suárez, 2020). Similar results were found through analysis of PISA 2006 data, confirming that science students who report engaging in low levels of inquiry activities show above-average levels of science literacy (McConney et al, 2014).…”
Section: Research Findings Regarding Inquiry-related Learning Activit...mentioning
confidence: 99%